1991
DOI: 10.21236/ada239981
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology of Combined Radiation Injuries: A Review and Analysis of the Literature on Non-Human Research

Abstract: Publ reporting burden for thiscollection of Infom tion is estmlted to average 1 hour p repiolns Including the time for reviewing instructions, serchinig existing data sOurces gathering and maintaining the "dt neded. Approved for public release; distribution is unlimited. ABSTRACT (Maximum 200 words)One hundred and seventy one references applicable to determining the effect of tactical nuclear weapons on military personnel have been reviewed, and the signifi-ant conclusions are reported. The study reviews the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Due to uncertainty in radiation effects on the vascular epithelium at high doses of radiation, a statistical model is used to predict lethality from radiation dose greater than about 4 Gy. The combined injury probit model was adapted from experimental animal data on combined injury (Alpen 1954, Baum 1991, which were extrapolated based on comparable equivalent human doses for each of the exposures used in the animal studies (Stricklin 2013c). The extrapolations were made using known dose-response curves for each species and each insult, radiation and burn.…”
Section: Modified Lethality With Standard Carementioning
confidence: 99%
See 1 more Smart Citation
“…Due to uncertainty in radiation effects on the vascular epithelium at high doses of radiation, a statistical model is used to predict lethality from radiation dose greater than about 4 Gy. The combined injury probit model was adapted from experimental animal data on combined injury (Alpen 1954, Baum 1991, which were extrapolated based on comparable equivalent human doses for each of the exposures used in the animal studies (Stricklin 2013c). The extrapolations were made using known dose-response curves for each species and each insult, radiation and burn.…”
Section: Modified Lethality With Standard Carementioning
confidence: 99%
“…Historical data from Hiroshima show that 65-70% of injured persons are expected to have combined injuries (Geiger 1964, Goans 2009. Experimental data has shown that radiation, combined with other injuries, shortens the onset of symptoms, exacerbates symptoms, causes synergistic increases in mortality, and impairs wound healing (Messerschmidt 1965, Baum 1991. To improve our understanding of human response to combined injury, updated models of radiation combined injury are needed.…”
Section: Introductionmentioning
confidence: 99%